Effect of vanadium addition and cryogenic treatment on the development of carbidic austempered ductile iron - Subham P.S.; Chakrabarty I. (My University, 2025)
The present study has been carried out with an objective to evaluate the effects of additions of vanadium to develop CADI structure. Further improvement in wear properties may be achieved with a cryogenic treatment. In view of this, the iron was subjected to cryogenic quenching in dry ice bath at -50°C subsequent to austempering. The effects are characterized by optical and scanning electron microscopy, hardness and impact toughness measurement and the study of dry sliding wear behavior. © 2016, The WFO (The World Foundry Organization Ltd). All rights reserved.